Painting Souvenirs of Italianicity - Speed, Isabella Maria Louise (Curtin University, 2020)
‘Souvenirs of Italianicity’ investigates the complexities of souvenirs within the domestic every day, and the potential of still life painting to engage with and to reflect on felt experiences surrounding these objects. The souvenirs that are the subject of the painting project are miniature reproductions of iconic sculptures from the old masters that quietly reside within the home of my family, not to pay tribute to the artists, but as objects embedded with hereditary significance.